2020
DOI: 10.1002/nop2.677
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of person‐ and family‐centred care transition interventions on patient‐ oriented outcomes: A systematic review

Abstract: Aim The aim was to critically analyse the body of evidence regarding the effectiveness of PFCC transition interventions on the quality of care and the experience of patients. Design We conducted a systematic review using the Cochrane Handbook's guidelines and adhered to a standardized reporting format: Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA). Methods Four databases and grey literature were searched. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…13 Despite the promise of PFCC, a recent review on care transitions reported a mixed effect of the impact of PFCC on patient-oriented outcomes leading the authors to reflect on the core components of the approach, and conclude that PFCC interventions must incorporate several core components to successfully improve transition outcomes. 14 Shared decision-making (SDM) is often viewed as one of the core components of PFCC. 15 SDM is a collaborative approach to decision-making, whereby health professionals and patients consider options and evidence together before making joint decisions.…”
Section: Open Accessmentioning
confidence: 99%
“…13 Despite the promise of PFCC, a recent review on care transitions reported a mixed effect of the impact of PFCC on patient-oriented outcomes leading the authors to reflect on the core components of the approach, and conclude that PFCC interventions must incorporate several core components to successfully improve transition outcomes. 14 Shared decision-making (SDM) is often viewed as one of the core components of PFCC. 15 SDM is a collaborative approach to decision-making, whereby health professionals and patients consider options and evidence together before making joint decisions.…”
Section: Open Accessmentioning
confidence: 99%
“…While many interventions aim to help address poor post-discharge outcomes stemming from poor communication such as self-care behaviors or emergency department visits and readmissions [1][2][3], few have evaluated the impact on patient experience [24][25][26][27]. Our paper is one of the first to use Canadian patient experience measures to evaluate its association with the widespread implementation of a novel discharge communication tool.…”
Section: Discussionmentioning
confidence: 99%
“…While many interventions aim to help address poor post-discharge outcomes stemming from poor communication such as self-care behaviors or emergency department visits and readmissions [ 1 – 3 ], few have evaluated the impact on patient experience [ 25 28 ]. Our paper is one of the first to use Canadian patient experience measures to evaluate its association with the widespread implementation of a novel discharge communication tool.…”
Section: Discussionmentioning
confidence: 99%